De la Praia da Estação au Conseil municipal de la culture : Mobilisations citadines et droit à la ville à Belo Horizonte (Minas Gerais, Brésil) - Pauline Bosredon; Flavio Carsalade (Confins)
Since the early 2000s, the Municipality of Belo Horizonte has sought to convert the station area into a cultural district. To this end, the mayor Marcio Lacerda (2009-2016) ordered all public gatherings to be banned on the station square, in order to protect its heritage. This article analyses the different paths followed for claiming the right to the city, from original street mobilisations to institutions of participation. After discussing the protest movement, the article deals with the creation of new negotiation channels with the population and highlights how the institutionalisation of social protest tends to weaken the richness of alternative forms of expression.